Project-Based Learning in Teaching Amplitude Modulation Techniques to Enhance Vocational High School Student Competencies - Laila, Nur; Rahmania, Dian Ayu Lailatul; Tambunan, Kezya Marisca Eunice; Ripalta, Amelia Esa; Jatmiko, Farizi Afdhal (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
Amplitude Modulation (AM) is a fundamental concept in analog communication systems and a core topic in vocational electronics education. However, many students struggle to grasp the abstract nature of AM theory when taught through conventional methods. This article presents the development of an innovative instructional model based on Project-Based Learning (PjBL) to support students’ understanding of amplitude modulation through hands-on activities. The learning model guides students in constructing and analyzing AM circuits using basic electronic components and simulation tools. The design process emphasizes inquiry, collaboration, and experimentation, enabling students to explore AM signal behavior in practical contexts. The instructional materials include project worksheets, simulation tasks, and performance-based assessment rubrics. This model aims to bridge the gap between theory and practice, foster technical competencies, and enhance student engagement in vocational high schools. The proposed design is ready for further implementation and validation in real classroom environments.